2022
DOI: 10.3390/children9121902
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Volumetric Bone Mineral Density of the Spine in Adolescent Rett Girls with Scoliosis

Abstract: In advanced Rett syndrome (RTT), limited or complete loss of ambulation, nutritional problems and scoliosis are unfavorable factors for bone mineral density (BMD). Still, there are few data available in this research area. Spinal quantitative computed tomography (QCT) allows an exact measurement of the volumetric BMD (vBMD) in this patient group. Two examiners measured vBMD of thoracic and lumbar vertebrae on asynchronous calibrated CTs that were acquired prior to surgical scoliosis correction (n = 21, age 13.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…The loss of the mechanical factor at a pediatric age can affect skeletal development and the achievement of an adequate bone mass peak [35]. The reduction in walking capacity or complete immobility leads to a reduction in bone mineral density, resulting in increased fractures for minor trauma [36]. Similarly, in a previous study by Presedo A et al that identified a risk factor for fracture in a population of patients with cerebral palsy, the most often affected sites were the distal femur or proximal tibia [37].…”
Section: Pathophysiology Of Bone Fragility In Patients With Rett Synd...mentioning
confidence: 99%
“…The loss of the mechanical factor at a pediatric age can affect skeletal development and the achievement of an adequate bone mass peak [35]. The reduction in walking capacity or complete immobility leads to a reduction in bone mineral density, resulting in increased fractures for minor trauma [36]. Similarly, in a previous study by Presedo A et al that identified a risk factor for fracture in a population of patients with cerebral palsy, the most often affected sites were the distal femur or proximal tibia [37].…”
Section: Pathophysiology Of Bone Fragility In Patients With Rett Synd...mentioning
confidence: 99%
“…After the regression phase, in the third pseudostationary stage, the disorder is mainly stable, but seizures, ataxia, and scoliosis appear. The last phase, by about 10 years of age, is the final late motor deterioration stage, scoliosis worsens, and mobility is often so severely limited that most patients will require the use of a wheelchair (6)(7)(8)(9).…”
mentioning
confidence: 99%